WAYS TO INCREASE THE EFFICIENCY OF MANAGEMENT OF EDUCATIONAL PROCESSES USING INFORMATION TECHNOLOGIES (Barqaror Taraqqiyot va Rivojlanish Tamoyillari, 2023)
This article provides information on ways to effectively manage employees in educational institutions, planning, organizing, assigning, motivating, leading, coordinating, and using information technologies.